Penilaian Kinerja Karyawan Menggunakan Metode Maut pada PT. Grand Sehat Auto Pro Clinic Berbasis Web - Patria, M. Bintang; Ok Muhammad Ihsan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
PT. Grand Sehat Pro Auto Clinic is a company that focuses on services in the automotive sector, especially for car maintenance, repair, and painting services. The many fields provided make PT. Grand Sehat Pro Auto Clinic has a large staff. A problem that often occurs at PT. Grand Sehat Pro Auto Clinic is that employee performance assessments in the company are still carried out with one criterion, namely attendance criteria, without considering other criteria. The lack of transparency in employee work values leads to negative perceptions and reduces employee trust in management. In addition, the system for assessing employee performance is still carried out using books so that the process is very long. To overcome these problems, PT. Grand Sehat Pro Auto Clinic requires a performance assessment system for employees that includes multiple criteria to ensure more accurate assessment results. The results of the employee performance assessment using the MAUT method ensure that the assessment is well systematized through predetermined criteria.